2021
DOI: 10.1177/15910199211003017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of flow diverters in posterior circulation aneurysms and comparison with their efficacy in anterior circulation aneurysms: A systematic review and meta-analysis

Abstract: Purpose We aimed to assess the efficacy and safety of flow-diverter stents (FDs) in the management of posterior circulation cerebral aneurysms and compare FD efficacy between anterior and posterior circulation aneurysms. Methods We searched the PubMed, Scopus, Cochrane, and Web of Science databases for relevant studies through March 2020. Studies assessing FDs for posterior circulation aneurysms that included ≥20 treated aneurysms were included. Moreover, the studies compared FD efficacy between anterior and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In the present case, although the aneurysm remained even one year after flow-diverting stent placement, the aneurysm decreased in size and remained unruptured. Predictive factors were reported, such as older age (>70 years),[ 12 , 19 ] aneurysm with mass effect, aneurysm location other than vertebral artery,[ 1 ] and fusiform morphology. [ 19 ] These factors were consistent with the present case and seemed to be the cause of incomplete occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, although the aneurysm remained even one year after flow-diverting stent placement, the aneurysm decreased in size and remained unruptured. Predictive factors were reported, such as older age (>70 years),[ 12 , 19 ] aneurysm with mass effect, aneurysm location other than vertebral artery,[ 1 ] and fusiform morphology. [ 19 ] These factors were consistent with the present case and seemed to be the cause of incomplete occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Shifting to ow-diverters, they are currently gaining signi cant attention, but results for aneurysms of the posterior circulation are still not completely encouraging. [29][30][31] For complex aneurysms, when conventional strategies are unsuitable, considering the outcomes, open surgery revascularizations are an adequate option for skilled neurosurgeons, 32 mainly in limited-resource countries. 15 When comparing endovascular to surgical approaches for PICA aneurysms, Saal-Zapata et al demonstrated that the literature, despite extensive, carries a serious risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis evaluating the efficacy of FDs in posterior compared to anterior circulation aneurysms, posterior circulation aneurysms were found to be effectively treated using FDs, with comparable occlusion rates to those in anterior circulation aneurysms. However, the risk of periprocedural complications was not negligible ( 41 ). Early studies have reported higher complication rates associated with the use of FDs in the posterior circulation ( 42 45 ).…”
Section: Discussionmentioning
confidence: 99%